Are climate risks encouraging cover crop adoption among farmers in the southern Wabash River Basin?. (March 2021) - Yoder, Landon; Houser, Matthew; Bruce, Analena; Sullivan, Abigail; Farmer, James
Highlights: Climate-driven risks were an emerging but limited driver of cover crop adoption. Farmers depicted adoption as creating tradeoffs rather than win-win outcomes. Climate change may encourage or discourage adoption because of tradeoffs. Outreach should prioritize involving farmers in shared problem-solving. Policy changes should help farmers manage adoption tradeoffs to prevent abandonment. Abstract: Cover crops represent a potential win-win opportunity to promote climate resilience by helping farmers adapt to climate risks while simultaneously mitigating multiple environmental impacts from agriculture. However, cover crop adoption rates are increasing slowly and cover less than 5% of U.S. croplands. In contrast, several Indiana counties in the southern Wabash River Basin have cover crops on more than 20 % of farmland. This qualitative study draws on 33 semi-structured interviews with farmers to understand whether climate risks are driving the above-average rates of adoption in this area. Our purposive sample of farmers was guided by whether they farmed flood-prone areas along the White and Wabash Rivers, thus making them especially sensitive to increasing flood risks from climate change. We found that while climate risks, particularly intensifying rainfall events, were a factor in some cases, most adoption was a longstanding effort to control wind-erosion on hilly areas with sandy soils. We also found that farmers experienced challenges with adoption following successful establishment of cover crops tied to climate-driven ecosystem responses. Greater spring precipitation delayed cash crop planting because of moisture retention and intensified pest pressures from increased habitat has caused replanting of cash crop seeds. Responses indicate that climate risks have mixed effects that may either discourage or encourage cover crop adoption depending on whether future outreach and policy interventions can help farmers overcome the adoption challenges they encounter.